Pengaruh Pelatihan Dan Pengembangan SDM Terhadap Kepuasaan Kerja Dan Dampaknya Terhadap Kinerja Karyawan PT. Sari Melati Kencana, Tbk. Lippo Cikarang - Muhammad Rafly; Raniasari Bimanti Esthi (Peneliti.net, 2023)
The purpose of this study aims to determine the effect of HR training and development on job satisfaction and its impact on employee performance at PT. Sari Melati Kecana, TBk, Lippo Cikarang. This research method uses a quantitative method with a population using pizza hut employees, Lippo Cikarang, Tbk. With a sample of 63 people. data analysis using path analysis with partial and simultaneous hypothesis testing. The results of this study first show that training with a coefficient value of 0.500 and a P-value of 0.013 is smaller than 0.05, indicating that training has a positive and significant effect on job satisfaction at PT. Sari Melati Kencana. TbK, Lippo Cikaran. The results of the second hypothesis test show that HR Development with a coefficient value of 0.372 and a P-Values value of 0.075 is smaller than 0.05, indicating that the Work Environment does not have a positive and significant influence on Job Satisfaction at PT. Sari Melati Kencana. TbK, Lippo Cikarang. The results of the third hypothesis test show that Job Satisfaction with a coefficient value of 0.902 and a P-Values value of 0.000 is smaller than 0.05, indicating that Job Satisfaction has a positive and significant influence on Employee Performance at PT. Sari Melati Kencana. Tbk, Lippo Cikarang